Analisis Komparatif Kinerja LSTM, BiLSTM, dan LSTM-AM dalam Prediksi Harga Saham Syariah - Muhamad Ramadhan Kamal; Rahman Taufik; Ridho Sholehurrahman; Tristiyanto .; Bita Parga Zen (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2026)
The continuously evolving Sharia stock market necessitates more accurate price modeling due to high volatility, regime shifts, and outliers that frequently disrupt investment decision-making processes. This study aims to comparatively evaluate the performance of three deep learning algorithms—LSTM (Long Short-Term Memory), BiLSTM (Bidirectional LSTM), and LSTM-AM (LSTM with Attention Mechanism)—in predicting Sharia stock prices. The research method utilizes daily closing price data from five Indonesian Sharia-compliant issuers (ANTM, ERAA, KLBF, SMGR, and WIKA) spanning the period of December 2016 to December 2021. The data underwent preprocessing using Robust Scaling and was structured into time series with a 60-day window. Model evaluation was conducted via window-based cross-validation with the results show that BiLSTM delivered the best performance with an average MAPE of 9.41% and RMSE of 249.956. This performance was followed by LSTM (MAPE 11.87%) and LSTM-AM as the lowest (MAPE 19.58%). These findings provide a clear understanding of the effectiveness of each architecture in predicting dynamic Sharia stock prices, indicating that increasing model complexity (LSTM-AM) does not always guarantee better accuracy in this domain. Consequently, BiLSTM can be considered the superior model for more stable prediction.